Administration of Candida Albicans to Dextran Sulfate Solution Treated Mice Causes Intestinal Dysbiosis, Emergence and Dissemination of Intestinal Pseudomonas Aeruginosa and Lethal Sepsis. Issue 2 (February 2020) - Hiengrach, Pratsanee; Panpetch, Wimonrat; Worasilchai, Navaporn; Chindamporn, Ariya; Tumwasorn, Somying; Jaroonwitchawan, Thiranut; Wilantho, Alisa; Chatthanathon, Piraya; Somboonna, Naraporn; Leelahavanichkul, Asada
Abstract : ABSTRACT: The influence of gut fungi in chronic colitis was investigated by repeated oral administration of Candida albicans in a 3% dextran sulfate solution (DSS) induced-colitis mouse model. Candida administration in the DSS (DSS+ Candida ) model enhanced the mortality rate and induced bacteremia (without candidemia) resulting from a gut perm-selectivity defect despite similar diarrheal severity in mice treated with DSS alone. The dominant fecal bacteria in DSS+ Candida and DSS alone mice were Pseudomonas spp. and Enterobacter spp., respectively, implying that Candida induced gut dysbiosis. Interestingly, chloramphenicol-resistant bacterial colonies, predominantly Pseudomonas spp., appeared in the feces and blood of DSS+ Candida mice (not the DSS alone group) during fungal culture. These antibiotic-resistant bacteria were also isolated, ex vivo, by incubating mouse feces with DSS and heat-killed Candida or (1→3)-β-D-glucan, suggesting bacterial fermentation on fungi. Administration of Pseudomonas aeruginosa isolated from chloramphenicol-resistant bacteria in the DSS +Candida model enhanced the severity of disease, and increased growth of isolated P aeruginosa in blood agar containing heat-killed Candida was demonstrated. These data suggested the selection of a highly virulent bacterial strain following fecal Candida presentation in the gut. Additionally, reduction of fecal fungi with fluconazole decreased the burden of chloramphenicol-resistant bacteria, attenuating the severity of DSS+ Candida . In conclusion, gut Candida induced bacteremia in the DSS model through an inflammation-induced gut perm-selectivity defect and facilitated the growth of some gut bacteria. Treatment strategies aimed at reducing gut fungi could attenuate disease severity. Further investigation of gut fungi in inflammatory bowel disease is warranted. Abstract : Supplemental Digital Content is available in the text